Effectiveness of lukewarm water compress on reduction of breast pain and breast engorgement among post-cesarean section mothers - Soni Chauhan; Kumari Nutan; Monica Agrawal; Surya Kant Tiwari (Wolters Kluwer Medknow Publications, 2023)
Objective: The study aimed to assess the effectiveness of lukewarm water compress on breast pain and breast engorgement among post-cesarean primiparous mothers. Materials and Methods: This quasi-experimental posttest-only design was conducted with 60 post-cesarean section primiparous mothers between October 2018 and January 2019. A simple random sampling technique was used to allocate 30 participants to both experimental and control groups. The experimental group received lukewarm water compress using a sponge cloth for 20 min twice a day on the second, third, and fourth postnatal days. The control group received routine hospital care. Breast pain and engorgement were assessed using the Visual Analog Pain Scale and Breast Engorgement Assessment Scale on the third, fourth, and fifth postnatal days. Results: Significant differences were observed between the experimental and control groups on day 1 and day 3 in terms of breast pain and engorgement scores among post-cesarean section mothers (P < 0.001). In addition, no statistically significant differences were found between sociodemographic and breastfeeding parameters and breast pain and engorgement (P > 0.05). Conclusion: Lukewarm water compress is effective in reducing breast pain and engorgement in post-cesarean primiparous mothers. Future research can include randomized controlled trials to evaluate the effectiveness of different therapies in treating breast pain and engorgement.